Amphiphilic olefin block copolymers synthesized by successive coordinative chain transfer and ring-opening polymerizations. (15th April 2022) - Jamali, Farhad; Hassanian-Moghaddam, Davood; Ahmadjo, Saeid; Mortazavi, Seyed Mohammad Mahdi; Maddah, Yasaman; Ahmadi, Mostafa
Graphical abstract: Highlights: Amphiphilic ethylene/caprolactone block copolymers are synthesized. A two-step synthesis strategy allows independent control over blocks' lengths. A microphase separated morphology with tri-crystal structure is formed at the solid state. Microphase separation cause deviation from the terminal behavior at the molten state. Abstract: Introducing polarity is a necessity for widening the application scope of polyolefins specifically for developing biocompatible products. To this end, we exploit a two-step polymerization process to synthesize poly(ethylene‑ b ‑caprolactone) PE‑PCL block copolymers, which contain both polar and non-polar segments. First ethylene is polymerized by a generic metallocene catalyst in the presence of ZnEt2 as the chain transfer agent according to the coordinative chain transfer polymerization (CCTP) technique. Terminal zinc atoms are subsequently replaced by hydroxyl groups (PE‑OH) by exposing dormant polymer chains to oxygen. Afterward, ring-opening polymerization (ROP) of ε‑caprolactone is initiated by PE‑OH to form PE‑PCL block copolymers. Successful formation of both blocks is verified by FTIR and NMR spectroscopy. The presence of PCL blocks greatly lowers the crystallinity of ethylene sequences according to XRD and DSC results. Moreover, a second type of PE crystals with more chain folds and lower lamella thickness is found in block copolymers, which is absent in the equivalent physical blend. The diverse crystal structure of block copolymers suggest that phase separation exists between PE and PCL segments. The SEM image of the equivalent physical blend confirms the tendency of PCL and PE chains to phase separate, and infers a compatibilization in the presence of PE‑PCL block copolymers. This phase separation is detected by rheological measurements, as well, where block copolymers show deviations from Maxwell behavior in the terminal relaxation zone at low frequencies. Rheology results also show that the order-disorder transition temperature ( TODT ) of these block copolymers is higher than 180 °C. These results provide a clear picture from the morphology and utility of such block copolymers specifically for compatibilizing blends of polar polymers and non-polar polyolefins, which significantly broaden the utility of polyolefins.